Zionism, Orientalism and Magic: The “Superstitious Beliefs” of the Sephardic Community in Jerusalem in “Zionistic” Eyes - Zinger, Nimrod (Jewish Thought, 2025)
This article focuses on the representations of “superstitious beliefs” of the Sephardic Jews in Jerusalem, as described by various Zionist figures such as Eliezer Ben-Yehuda, Avraham Shmuel Hirschberg, and others in the late nineteenth and early twentieth centuries. The study demonstrates that the rejection of the magical beliefs within the Sephardic worldview played a central role in the Zionist-Orientalist discourse concerning the Jews of the “East.” The roots of this negative attitude toward magic can already be traced to the literature of the Haskalah, which frequently mocked the magical beliefs of Eastern European Jews, viewing them as evidence of their “Asiatic primitiveness.” By examining the discourse surrounding various Sephardic “superstitious” practices, most notably the Indulco ritual, the article argues that the denouncement of magic served as a key mechanism in constructing a clear hierarchy within the emerging Jewish nation, distinguishing between “enlightened and rational” Jews and “backward, Oriental” Jews deemed in need of “reform.”